Freeze-dried powder composition with anti-aging and repairing functions and preparation method of freeze-dried powder composition
By using lyophilized powder compositions prepared with ingredients such as polyoxyethylene stearate, the penetration and multiple damage problems of existing anti-aging products are solved, and the efficient moisturizing and stability of lyophilized powder is achieved, and the aging process is delayed.
Patent Information
- Application Number
- CN202411412825.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing anti-aging products are difficult to penetrate under the limitation of the skin barrier, and the bioavailability of oral supplements is low. Most products only have a single function, which fails to effectively solve the problem of multiple skin damage caused by aging. At the same time, freeze-dried powder products are being preserved and During transportation, the active ingredients are prone to inactivate or degrade, and poor solubility affects the effect.
Prepared by polyoxyethylene stearate, propylene glycol, squalane, acrylamide grafted hydroxyethyl cellulose, sodium citrate, vitamin E, vitamin C, natural extract and polyethylene glycol-trehalose co-crystals The lyophilized powder composition combines the active ingredient by forming a glassy structure and the wetting properties of polyethylene glycol by trehalose, thereby improving emulsification ability and moisturizing effect.
It significantly improves the moisturizing performance and stability of freeze-dried powder, ensures that the active ingredients do not degrade during freeze-drying and storage, quickly rehydrate to form a uniform emulsion, provides a long-term moisturizing layer, delays the aging process and improves skin moisture.
Smart Images

Figure BDA0005078492510000101 
Figure BDA0005078492510000111 
Figure HDA0005078492520000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of beauty cosmetics, and specifically relates to a freeze-dried powder composition with anti-aging and repairing functions and a preparation method thereof. Background Art
[0002] In recent years, with the development of society and the improvement of living standards, people's attention to health and beauty has been increasing, especially in the field of anti-aging and skin repair, and the market demand is growing. Aging is a complex biological process, which is affected by multiple factors such as genetics, environment, and lifestyle, and manifests as skin sagging, wrinkles, pigmentation, etc. In response to this challenge, a variety of anti-aging products have appeared on the market, including creams, essences, oral supplements, etc. However, these traditional anti-aging products have certain limitations in practical applications. On the one hand, due to the limitations of the skin barrier, the active ingredients in topical products are often difficult to penetrate into the dermis, affecting their actual effects. On the other hand, the bioavailability of the active ingredients of oral supplements after metabolism in the body is often low, resulting in limited effects. In addition, existing anti-aging products mostly focus on single functions such as moisturizing and anti-oxidation, and fail to effectively solve the problem of multiple skin damage caused by aging.
[0003] As an emerging formulation technology, freeze-dried powder technology maintains the activity and stability of the ingredients to the greatest extent by rapidly freezing and drying the active ingredients at low temperatures. When in use, by dissolving the freeze-dried powder in a solvent, the function of the active ingredient can be immediately restored to ensure that it has the best effect when in use. There are still some shortcomings in the freeze-dried powder products currently on the market. For example, although freeze-drying technology can protect the active ingredients to a certain extent, in actual applications, many existing freeze-dried powder products still have problems with inactivation or degradation of active ingredients during long-term storage and transportation, especially in environments with large fluctuations in temperature and humidity; many freeze-dried powder products need to be dissolved in specific solvents when used, but due to the large molecular weight or poor solubility of some active ingredients, the skin's absorption rate of these ingredients is limited, thereby affecting the overall efficacy of the product. Therefore, based on the above problems, it is extremely necessary to develop a freeze-dried powder composition with good biocompatibility, excellent solubility and anti-aging repair function. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a freeze-dried powder composition with anti-aging and repairing functions and a preparation method thereof.
[0005] The technical effect described in the present invention is achieved through the following technical scheme: a freeze-dried powder composition with anti-aging and repair functions, comprising the following raw materials: 1 to 2 parts of polyoxyethylene stearate, 10 to 15 parts of propylene glycol, 5 to 10 parts of squalane, 1 to 2 parts of acrylamide grafted hydroxyethyl cellulose, 0.1 to 0.5 parts of sodium citrate, 0.5 to 1 part of vitamin E, 0.5 to 1 part of vitamin C, 1 to 2 parts of natural extracts, 5 to 10 parts of polyethylene glycol-trehalose eutectic and 80 to 100 parts of deionized water.
[0006] Preferably, the specific preparation steps of the acrylamide grafted hydroxyethyl cellulose are as follows:
[0007] A1: Add hydroxyethyl cellulose to deionized water and stir until completely dissolved to obtain a 2wt% hydroxyethyl cellulose solution; add acrylamide to deionized water and stir until completely dissolved to obtain a 2wt% acrylamide solution; dissolve ammonium persulfate and N,N'-methylenebisacrylamide in deionized water to obtain an initiating solution;
[0008] A2: Add the initiating solution prepared in step A1 to the hydroxyethyl cellulose solution, continue stirring to mix evenly, then add the acrylamide solution prepared in step A1, stir and mix evenly, heat in a water bath to control the temperature to 60-70°C, react for 4-6 hours, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose.
[0009] Preferably, the ratio of the amount of ammonium persulfate, N,N'-methylenebisacrylamide and deionized water used in step A1 is 0.04-0.06 g: 0.02 g: 30 mL.
[0010] Preferably, the volume ratio of the initiating solution, the hydroxyethyl cellulose solution and the acrylamide solution in step A2 is 1:1:1-2.
[0011] Preferably, the specific preparation steps of the polyethylene glycol-trehalose co-crystal are as follows:
[0012] B1: adding polyethylene glycol to deionized water, stirring and mixing evenly to obtain a 5-10 wt % polyethylene glycol solution; adding trehalose to deionized water, stirring and mixing evenly to obtain a 5-10 wt % trehalose solution;
[0013] B2: Add the trehalose solution prepared in step B1 to the polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 60-70°C at 5°C / min, then maintain the temperature with stirring for 10-20 min, cool naturally to room temperature, adjust the pH to neutral, perform ultrasonic treatment, set the parameters to 20-40 kHz, power to 30-60 W, time to 10-20 min, filter, wash with cold ethanol at 0°C, and freeze-dry at -40°C in a vacuum until constant weight is obtained to obtain polyethylene glycol-trehalose co-crystals.
[0014] Preferably, the volume ratio of the trehalose solution to the polyethylene glycol solution in step B2 is 1:1 to 1.5.
[0015] Preferably, the natural extract is prepared by mixing green tea, turmeric, Centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 by conventional technical means.
[0016] Preferably, another aspect of the present invention is to provide a method for preparing a freeze-dried powder composition having anti-aging and repairing functions, and the specific preparation steps are as follows:
[0017] S1: Squalane, vitamin E and polyoxyethylene stearate are mixed by weight, heated and stirred at 60-70° C. to completely dissolve them, and obtain an oil phase; propylene glycol and sodium citrate are dissolved by weight in deionized water, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated in a water bath to 50-60° C., stirred until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase;
[0018] S2: slowly adding the oil phase prepared in step S1 to the water phase, stirring at 500-800 rpm for 30-60 min at 60-70° C. using a magnetic stirrer, and then homogenizing for 3-5 times, setting parameters to 300-500 bar, temperature to room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stirring again at 500-1000 rpm for 10 min to obtain emulsion A;
[0019] S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals, continue stirring until uniformly dispersed, and obtain emulsion B; cool the emulsion B to 0°C at a rate of 0.5-1°C / min, then cool it to -40--50°C at a rate of 1-2°C / min, maintain the temperature for 1-2h, then heat it to room temperature and dry it to constant weight to obtain a lyophilized powder composition.
[0020] The beneficial effects of the present invention are as follows:
[0021] The anti-aging and repair-promoting freeze-dried powder prepared by the present invention using polyoxyethylene stearate, propylene glycol, squalane, acrylamide-grafted hydroxyethyl cellulose, sodium citrate, vitamin E, vitamin C, natural extracts and polyethylene glycol-trehalose co-crystals has a significant synergistic effect. During the freeze-drying process, the polyethylene glycol-trehalose co-crystals can effectively protect sensitive active ingredients from damage by temperature, oxygen and mechanical stress, wherein trehalose forms a glassy structure to wrap the active ingredients, providing a physical barrier to prevent them from denaturation or degradation, while polyethylene glycol helps to form a stable amorphous matrix through its flexibility and wettability, further reducing the degradation or failure of the active ingredients. Trehalose also inhibits the formation of large ice crystals during the freeze-drying process to reduce mechanical stress damage. At the same time, polyethylene glycol improves the structural properties of the matrix to ensure that the freeze-dried powder can quickly absorb water and dissolve evenly when rehydrated.
[0022] In addition, the hydrophilicity of polyoxyethylene stearate and polyethylene glycol works together to enhance emulsification ability and stability. The hydrophilicity and wettability of polyethylene glycol enable it to quickly enter the aqueous phase, assist the emulsifier in wrapping the oil phase particles, and form a uniform oil droplet dispersion system. At the same time, trehalose provides additional stabilization in the aqueous phase to prevent oil droplets from aggregating and stratifying, thereby prolonging the stability of the emulsion. After rehydration, the combination of polyethylene glycol and trehalose provides a powerful moisturizing effect. Polyethylene glycol can quickly attract and retain moisture and form a moisturizing layer on the skin surface. Squalane further locks in moisture to form a good moisturizing barrier. In addition, propylene glycol, as a moisturizer, synergizes with these ingredients to significantly improve the moisturizing properties of the emulsion, allowing it to keep the skin moisturized for a long time after application.
[0023] After rehydration, the freeze-dried powder prepared by the present invention provides a strong moisturizing effect through the combination of polyethylene glycol and trehalose. Polyethylene glycol can quickly attract and retain moisture and form a moisturizing layer on the skin surface. Squalane further locks moisture to form a good moisturizing barrier. In addition, propylene glycol acts as a moisturizer and synergizes with these ingredients to significantly improve the moisturizing performance of the emulsion, so that it can keep the skin moisturized for a long time after application. Trehalose forms a protective matrix, and polyethylene glycol further reduces oxidative stress and protects the effectiveness of active ingredients. Trehalose in the co-crystal can isolate the influence of oxygen and light, maintain its activity, and prevent oxidative degradation during freeze-drying and storage. This ensures that the vitamin can effectively neutralize free radicals when used, reduce the damage of oxidative stress to skin cells, and thus delay the aging process.
[0024] Acrylamide grafted hydroxyethyl cellulose as a thickener and emulsifier has excellent viscosity adjustment ability and emulsification stability. During the rehydration process, acrylamide grafted hydroxyethyl cellulose can quickly dissolve and form a stable emulsion, ensuring the uniform distribution of oil phases such as squalane and maintaining the long-term stability of the emulsion; in addition, acrylamide grafted hydroxyethyl cellulose can not only increase viscosity, but also has the characteristics of emulsification. It can work together with emulsifiers (polyoxyethylene stearate and polyethylene glycol) to further enhance the stability of the emulsion. The introduction of acrylamide increases the flexibility and reactivity of the molecular chain, so that it can better disperse and stabilize the oil droplets during the emulsion formation process and prevent the oil droplets from merging or agglomerating; at the same time, polyethylene glycol provides a silky texture in the emulsion, and trehalose enhances the moisturizing effect, making the emulsion not only easy to apply, but also forming a long-lasting soft and moisturizing layer on the skin. The co-crystals with rapid rehydration properties can form an emulsion under mild stirring conditions, reducing the obstacles to the work of the emulsifier. After adding water to the freeze-dried powder, the user only needs to gently stir it to obtain a stable and uniform emulsion, greatly simplifying the use process. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 It is a biocompatibility test diagram of the freeze-dried powder composition prepared in Examples 1 to 4 of the present invention;
[0027] Figure 2 is the FTIR infrared spectrum of the polyethylene glycol-trehalose co-crystal prepared in Example 2 of the present invention;
[0028] Figure 3 It is a stability test chart of the freeze-dried powder composition prepared in Examples 2 to 3 of the present invention and Comparative Examples 1 to 3;
[0029] Figure 4 It is a DPPH free radical scavenging test graph of the freeze-dried powder composition prepared in Examples 2 to 3 of the present invention and Comparative Examples 1 to 3;
[0030] Figure 5 This is a skin moisturizing test of the freeze-dried powder compositions prepared in Examples 2 to 3 of the present invention and Comparative Examples 1 to 3. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0032] Example 1: A freeze-dried powder composition with anti-aging and repair functions, comprising the following raw materials: 1 part of polyoxyethylene stearate, 10 parts of propylene glycol, 5 parts of squalane, 1 part of acrylamide grafted hydroxyethyl cellulose, 0.1 part of sodium citrate, 0.5 part of vitamin E, 0.5 part of vitamin C, 1 part of natural extract, 5 parts of polyethylene glycol-trehalose co-crystal and 80 parts of deionized water.
[0033] 1. Preparation of acrylamide grafted hydroxyethyl cellulose:
[0034] A1: 10 g of hydroxyethyl cellulose was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% hydroxyethyl cellulose solution; 10 g of acrylamide was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% acrylamide solution; 0.4 g of ammonium sulfate and 0.2 g of N,N'-methylenebisacrylamide were dissolved in 300 mL of deionized water to obtain an initiating solution;
[0035] A2: Add 200 mL of the initiating solution prepared in step A1 to 200 mL of the hydroxyethyl cellulose solution, continue stirring and mixing, then add 200 mL of the acrylamide solution prepared in step A1, stir and mix, heat in a water bath to control the temperature to 60°C, react for 6 hours, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose;
[0036] 2. Preparation of polyethylene glycol-trehalose co-crystals:
[0037] B1: adding polyethylene glycol to deionized water, stirring and mixing evenly to obtain a 5wt% polyethylene glycol solution; adding trehalose to deionized water, stirring and mixing evenly to obtain a 5wt% trehalose solution;
[0038] B2: Add 200 mL of trehalose solution prepared in step B1 to 200 mL of polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 60°C at 5°C / min, then maintain the temperature and stir for 20 min, cool naturally to room temperature, adjust the pH to neutral, perform ultrasonic treatment, set the parameters to 20 kHz, power to 30 W, time to 20 min, filter, wash with cold ethanol at 0°C, and freeze-dry at -40°C in a vacuum until constant weight is obtained to obtain polyethylene glycol-trehalose co-crystals;
[0039] 3. The natural extract is prepared by mixing green tea, turmeric, Centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 by conventional technical means;
[0040] 4. Preparation of freeze-dried powder composition with anti-aging and repairing functions:
[0041] S1: Squalane, vitamin E and polyoxyethylene stearate are mixed according to weight parts, heated and stirred at 60°C to completely dissolve them, and an oil phase is obtained; propylene glycol and sodium citrate are dissolved in deionized water according to weight parts, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated to 50°C in a water bath, stirred thoroughly until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase;
[0042] S2: slowly adding the oil phase prepared in step S1 to the water phase, stirring at 500 rpm for 60 min at 60°C using a magnetic stirrer, and then homogenizing for 3 times, setting the parameters to 300 bar, the temperature to room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stirring again at 500 rpm for 10 min to obtain emulsion A;
[0043] S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals, continue stirring until uniformly dispersed, and obtain emulsion B; cool the emulsion B to 0°C at a rate of 0.5°C / min, then cool it to -40°C at a rate of 1°C / min, maintain the temperature for 2h, then heat it to room temperature and dry it to constant weight to obtain a lyophilized powder composition.
[0044] Example 2: A freeze-dried powder composition with anti-aging and repair functions, comprising the following raw materials: 2 parts of polyoxyethylene stearate, 15 parts of propylene glycol, 8 parts of squalane, 2 parts of acrylamide grafted hydroxyethyl cellulose, 0.5 parts of sodium citrate, 1 part of vitamin E, 1 part of vitamin C, 2 parts of natural extracts, 8 parts of polyethylene glycol-trehalose co-crystals and 100 parts of deionized water.
[0045] 1. Preparation of acrylamide grafted hydroxyethyl cellulose:
[0046] A1: 10 g of hydroxyethyl cellulose was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% hydroxyethyl cellulose solution; 10 g of acrylamide was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% acrylamide solution; 0.55 g of ammonium sulfate and 0.2 g of N,N'-methylenebisacrylamide were dissolved in 300 mL of deionized water to obtain an initiating solution;
[0047] A2: Add 200 mL of the initiating solution prepared in step A1 to 200 mL of the hydroxyethyl cellulose solution, continue stirring and mixing, then add 350 mL of the acrylamide solution prepared in step A1, stir and mix, heat in a water bath to control the temperature to 65°C, react for 6 hours, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose;
[0048] 2. Preparation of polyethylene glycol-trehalose co-crystals:
[0049] B1: Add polyethylene glycol to deionized water, stir and mix evenly to obtain a 10wt% polyethylene glycol solution; add trehalose to deionized water, stir and mix evenly to obtain an 8wt% trehalose solution;
[0050] B2: Add 200 mL of trehalose solution prepared in step B1 to 280 mL of polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 65°C at 5°C / min, then maintain the temperature with stirring for 15 min, cool naturally to room temperature, adjust the pH to neutral, perform ultrasonic treatment, set the parameters to 30 kHz, power to 45 W, time to 20 min, filter, wash with cold ethanol at 0°C, and freeze-dry at -40°C in a vacuum until constant weight is obtained to obtain polyethylene glycol-trehalose co-crystals;
[0051] 3. The natural extract is prepared by mixing green tea, turmeric, Centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 by conventional technical means;
[0052] 4. Preparation of freeze-dried powder composition with anti-aging and repairing functions:
[0053] S1: Squalane, vitamin E and polyoxyethylene stearate are mixed according to weight parts, heated and stirred at 65°C to completely dissolve them, and an oil phase is obtained; propylene glycol and sodium citrate are dissolved in deionized water according to weight parts, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated to 55°C in a water bath, stirred thoroughly until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase;
[0054] S2: slowly adding the oil phase prepared in step S1 to the water phase, stirring at 600 rpm for 50 min at 65°C using a magnetic stirrer, and then homogenizing for 5 times, setting the parameters to 450 bar, the temperature to room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stirring again at 800 rpm for 10 min to obtain emulsion A;
[0055] S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals and continue stirring until uniformly dispersed to obtain emulsion B; cool the emulsion B to 0°C at a rate of 1°C / min, then cool it to -50°C at a rate of 2°C / min, maintain the temperature for 1.5h, then heat it to room temperature and dry it to constant weight to obtain a freeze-dried powder composition.
[0056] Example 3: A freeze-dried powder composition with anti-aging and repair functions, comprising the following raw materials: 1.5 parts of polyoxyethylene stearate, 13 parts of propylene glycol, 8 parts of squalane, 1.5 parts of acrylamide grafted hydroxyethyl cellulose, 0.3 parts of sodium citrate, 0.8 parts of vitamin E, 0.8 parts of vitamin C, 1.5 parts of natural extracts, 8 parts of polyethylene glycol-trehalose co-crystals and 90 parts of deionized water.
[0057] 1. Preparation of acrylamide grafted hydroxyethyl cellulose:
[0058] A1: 10 g of hydroxyethyl cellulose was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% hydroxyethyl cellulose solution; 10 g of acrylamide was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% acrylamide solution; 0.5 g of ammonium sulfate and 0.2 g of N,N'-methylenebisacrylamide were dissolved in 300 mL of deionized water to obtain an initiating solution;
[0059] A2: Add 200 mL of the initiating solution prepared in step A1 to 200 mL of the hydroxyethyl cellulose solution, continue stirring and mixing, then add 300 mL of the acrylamide solution prepared in step A1, stir and mix, heat in a water bath to control the temperature to 70°C, react for 5 hours, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose;
[0060] 2. Preparation of polyethylene glycol-trehalose co-crystals:
[0061] B1: adding polyethylene glycol to deionized water, stirring and mixing evenly to obtain an 8wt% polyethylene glycol solution; adding trehalose to deionized water, stirring and mixing evenly to obtain a 10wt% trehalose solution;
[0062] B2: Add 200 mL of trehalose solution prepared in step B1 to 250 mL of polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 70°C at 5°C / min, then maintain the temperature with stirring for 15 min, cool naturally to room temperature, adjust the pH to neutral, perform ultrasonic treatment, set the parameters to 35 kHz, power to 50 W, time to 15 min, filter, wash with cold ethanol at 0°C, and freeze-dry at -40°C in a vacuum until constant weight is obtained to obtain polyethylene glycol-trehalose co-crystals;
[0063] 3. The natural extract is prepared by mixing green tea, turmeric, Centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 by conventional technical means;
[0064] 4. Preparation of freeze-dried powder composition with anti-aging and repairing functions:
[0065] S1: Squalane, vitamin E and polyoxyethylene stearate are mixed according to weight parts, heated and stirred at 70°C to completely dissolve them, and an oil phase is obtained; propylene glycol and sodium citrate are dissolved in deionized water according to weight parts, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated to 60°C in a water bath, stirred thoroughly until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase;
[0066] S2: slowly adding the oil phase prepared in step S1 to the water phase, stirring at 700 rpm for 40 min at 70°C using a magnetic stirrer, and then homogenizing for 4 times, setting the parameters to 400 bar, the temperature to room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stirring again at 700 rpm for 10 min to obtain emulsion A;
[0067] S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals, continue stirring until uniformly dispersed, and obtain emulsion B; cool the emulsion B to 0°C at a rate of 0.8°C / min, then cool it to -45°C at a rate of 1.5°C / min, maintain the temperature for 2h, then heat it to room temperature and dry it to constant weight to obtain a lyophilized powder composition.
[0068] Example 4: A freeze-dried powder composition with anti-aging and repair functions, comprising the following raw materials: 2 parts of polyoxyethylene stearate, 15 parts of propylene glycol, 10 parts of squalane, 2 parts of acrylamide grafted hydroxyethyl cellulose, 0.5 parts of sodium citrate, 1 part of vitamin E, 1 part of vitamin C, 2 parts of natural extracts, 10 parts of polyethylene glycol-trehalose co-crystals and 100 parts of deionized water.
[0069] 1. Preparation of acrylamide grafted hydroxyethyl cellulose:
[0070] A1: 10 g of hydroxyethyl cellulose was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% hydroxyethyl cellulose solution; 10 g of acrylamide was added to 500 mL of deionized water and stirred until completely dissolved to obtain a 2 wt% acrylamide solution; 0.6 g of ammonium sulfate and 0.2 g of N,N'-methylenebisacrylamide were dissolved in 300 mL of deionized water to obtain an initiating solution;
[0071] A2: Add 200 mL of the initiating solution prepared in step A1 to 200 mL of the hydroxyethyl cellulose solution, continue stirring and mixing, then add 400 mL of the acrylamide solution prepared in step A1, stir and mix, heat in a water bath to control the temperature to 70°C, react for 4 hours, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose;
[0072] 2. Preparation of polyethylene glycol-trehalose co-crystals:
[0073] B1: adding polyethylene glycol to deionized water, stirring and mixing evenly to obtain a 10 wt % polyethylene glycol solution; adding trehalose to deionized water, stirring and mixing evenly to obtain a 10 wt % trehalose solution;
[0074] B2: Add 200 mL of trehalose solution prepared in step B1 to 300 mL of polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 70°C at 5°C / min, then maintain the temperature and stir for 10 min, cool naturally to room temperature, adjust the pH to neutral, perform ultrasonic treatment, set the parameters to 40 kHz, power to 60 W, time to 10 min, filter, wash with cold ethanol at 0°C, and freeze-dry at -40°C in a vacuum until constant weight is obtained to obtain polyethylene glycol-trehalose co-crystals;
[0075] 3. The natural extract is prepared by mixing green tea, turmeric, Centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 by conventional technical means;
[0076] 4. Preparation of freeze-dried powder composition with anti-aging and repairing functions:
[0077] S1: Squalane, vitamin E and polyoxyethylene stearate are mixed according to weight parts, heated and stirred at 70°C to completely dissolve them, and an oil phase is obtained; propylene glycol and sodium citrate are dissolved in deionized water according to weight parts, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated to 60°C in a water bath, stirred thoroughly until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase;
[0078] S2: slowly add the oil phase prepared in step S1 to the water phase, stir at 800 rpm for 30 min at 70°C using a magnetic stirrer, and then perform homogenization cycle treatment 5 times, setting the parameters to 500 bar, the temperature to room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stir again at 1000 rpm for 10 min to obtain emulsion A;
[0079] S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals, continue stirring until uniformly dispersed, and obtain emulsion B; cool the emulsion B to 0°C at a rate of 1°C / min, then cool it to -50°C at a rate of 2°C / min, maintain the temperature for 1h, then heat it to room temperature and dry it to constant weight to obtain a lyophilized powder composition.
[0080] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that sucrose is used in Comparative Example 1 instead of polyethylene glycol-trehalose co-crystal.
[0081] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that hydroxyethyl cellulose is used in Comparative Example 2 instead of acrylamide-grafted hydroxyethyl cellulose.
[0082] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 3, except that polyoxyethylene stearate is not added in Comparative Example 3.
[0083] Performance Test:
[0084] Rehydration test: The freeze-dried powder compositions prepared in Examples 2 to 3 and Comparative Examples 1 to 3 were added to deionized water, 5 g of freeze-dried powder was added to 100 mL of deionized water, and gently stirred at room temperature. The time required for the freeze-dried powder to form an emulsion was recorded. After standing for 2 h, the appearance of the emulsion was observed to determine whether there was oil-water separation. The results were recorded as shown in Table 1.
[0085] Table 1. Rehydration test results of freeze-dried powder compositions
[0086]
[0087]
[0088] It can be seen from the results in Table 1 that the freeze-dried powder composition prepared by the present invention can be effectively rehydrated to form an emulsion in a short time. It can be seen from the results of Comparative Example 1 and Example 2 that sucrose does not have the ability of polyethylene glycol-trehalose co-crystal to synergistically stabilize the emulsion, and sucrose does not participate in the formation and stabilization of the emulsion, which seriously affects the stability and formation speed of the emulsion; from the results of Comparative Example 2 and Example 2, it can be seen that the thickening and stabilizing effects of hydroxyethyl cellulose are not as good as those of acrylamide-grafted hydroxyethyl cellulose, and hydroxyethyl cellulose causes the emulsion to be difficult to form and is prone to oil-water separation; from the results of Comparative Example 3 and Example 3, it can be seen that polyoxyethylene stearate, as the main emulsifier, is responsible for the mixing of the oil phase and the water phase, which indeed leads to the inability to form an emulsion.
[0089] Biocompatibility test: The freeze-dried powder composition samples prepared in Examples 1 to 4 (1 g dissolved in 20 mL of deionized water for rehydration) and the control group (DMEM culture medium) were evenly distributed in a 96-well plate with 16 wells per group of samples, and then the cultured Fibroblasts were diluted to 1×10 5 After 50 μL of 5 mg / mL of MTT solution was inoculated in a 96-well plate, the temperature was set at 37°C and the concentration of CO2 was 5%. After incubation for 48 hours, 50 μL of 5 mg / mL MTT solution was added, and the incubation was continued for 4 hours. The culture medium in the wells was aspirated, and 200 μL of dimethyl sulfoxide was added to the wells. The absorbance (OD value) was measured at 570 nm using an ELISA reader, and the activity percentage was measured [cell survival rate (%) = (OD value of the embodiment / OD value of the control group) × 100%]. Each sample was processed and analyzed three times, and the results were averaged. The results are shown in the figure. Figure 1 shown.
[0090] Depend on Figure 1 The results show that the freeze-dried powder composition prepared by the present invention has excellent biocompatibility, can effectively act on the skin, and will not cause harmful effects on the human body.
[0091] Spectrum test: The freeze-dried powder composition sample prepared in Example 2 of the present invention was rehydrated and coated on a potassium bromide substrate, and the spectrum was measured using an FTIR spectrometer. The results are as follows: Figure 2 shown.
[0092] Depend on Figure 2 The results show that in the spectrum of polyethylene glycol (PEG), at about 3400 cm -1 A wider absorption peak appeared around 1000-1800cm, representing the stretching vibration of the hydroxyl group (-OH) in the polyethylene glycol molecule. In the polyethylene glycol-trehalose co-crystal, this peak position changed and a wider peak appeared, indicating that hydrogen bonds were formed between trehalose and polyethylene glycol, resulting in changes in the intermolecular interaction, which effectively proved the formation of the co-crystal; in addition, the interaction between the two components of polyethylene glycol and trehalose resulted in the 1000-1800cm -1The positions of multiple characteristic peaks.
[0093] Stability test: The freeze-dried powder composition samples prepared in Examples 2 to 3 and Comparative Examples 1 to 3 were sealed according to commercial packaging and placed at a temperature of 25±2°C and a relative humidity of 60±5% for 6 months. Samples were taken at the 1st, 2nd, 3rd and 6th month of the test period to record changes in appearance and pH. The pH changes were as follows: Figure 3 shown.
[0094] Depend on Figure 3 As can be seen from the results, the freeze-dried powder composition prepared by the present invention can be effectively preserved for a long time in the accelerated test. From the results of Comparative Example 1 and Example 2, it can be seen that sucrose, as a carbohydrate substance without buffering capacity, is not as effective as polyethylene glycol-trehalose co-crystal in the formulation in stabilizing the emulsion. In addition, sucrose may degrade in aqueous solution over time to generate acidic substances (acetic acid), resulting in a gradual decrease in pH. From the results of Comparative Example 2 and Example 2, it can be seen that compared with acrylamide-grafted hydroxyethyl cellulose, hydroxyethyl cellulose has poor emulsion stability, resulting in slight decomposition and deterioration of some components in the emulsion system, resulting in a slight decrease in pH. From the results of Comparative Example 3 and Example 3, it can be seen that due to the lack of emulsifier, the oil phase and the aqueous phase cannot form a stable emulsion, resulting in stratification, oxidation of the oil phase components to generate acidic substances, decomposition of the components in the aqueous phase, and a rapid decrease in pH.
[0095] DPPH free radical scavenging test: Take 2mL of DPPH solution and 2mL of the sample solution to be tested (1g of the freeze-dried powder composition samples prepared in Examples 2 to 3 and Comparative Examples 1 to 3 are respectively dissolved in 20mL of deionized water), mix well, place in the dark for 30min, and measure the absorbance value at 517nm with anhydrous ethanol solution as a reference. The DPPH solution is a solution with a concentration of 0.1mM prepared with anhydrous ethanol as the solvent. Calculate the DPPH free radical scavenging rate (scavenging rate = [1-(absorbance of the mixture of sample and DPPH-absorbance of the sample solution without DPPH / absorbance of the solution containing only DPPH] × 100%), repeat the test 3 times, take the average value, and the results are as follows: Figure 4 shown.
[0096] Depend on Figure 4As can be seen from the results, the freeze-dried powder prepared by the present invention has excellent antioxidant properties and can effectively scavenge free radicals. From the results of Comparative Example 2 and Example 2, it can be seen that the DPPH free radical scavenging rate is significantly reduced in the absence of acrylamide-grafted hydroxyethyl cellulose that enhances the stability of the antioxidant; from the results of Comparative Example 3 and Example 3, it can be seen that due to the absence of polyoxyethylene stearate, the oil phase and the water phase cannot form a stable emulsion, resulting in an uneven distribution of (vitamin E, vitamin C and natural extracts) and a poor DPPH scavenging rate; from the above results, it can be seen that the rapid rehydration effectively reduces the time that the active ingredients are exposed to air and light, and helps protect sensitive active ingredients from oxidation and degradation.
[0097] Skin moisture content test: 20 healthy volunteers with no history of allergy to skin care products were selected. The volunteers were aged between 25 and 35 years old and randomly divided into test groups 1 to 2 and comparison groups 1 to 2. There was no gender limit, and each group had 5 people. The first test of the 5 groups of volunteers was measured without using skin care products. They only washed their faces with clean water in the morning and evening. The first test was carried out after 3 days, that is, the skin care products were used from the 4th day. After cleansing the face in the morning and evening every day, the lyophilized powder rehydrated solution described in Examples 2 to 3 and Comparative Examples 1 to 2 was used (1 g of the sample was dissolved in 20 mL of deionized water for rehydration). The method of use was as follows: Apply an appropriate amount on the face and pat until completely absorbed. Use the TEWL instrument to test the stratum corneum water loss of each subject 1 day before and 1 day after using the product. Then, test once every 3 days. Record the average stratum corneum water loss of each group of subjects when they first did not use skin care products, the average stratum corneum water loss of the first test when they started using the product, and the average stratum corneum water content tested once every 3 days. Test 4 times in total. Moisturizing property = (water loss before use - water loss after use) / water loss before use × 100%. The results are as follows Figure 5 shown.
[0098] Depend on Figure 5 As can be seen from the results, the freeze-dried powder preparation prepared by the present invention can effectively play a moisturizing and moisturizing role. From the results of Comparative Example 1 and Example 2, it can be seen that the polyethylene glycol-trehalose co-crystal can form a more stable moisturizing film on the skin surface, lock in moisture, and enhance the moisturizing effect; from the results of Comparative Example 2 and Example 3, it can be seen that there is no special film-forming and water-locking ability of acrylamide-grafted hydroxyethyl cellulose. This substitution leads to a decrease in the ability to form a moisturizing film and maintain moisture, resulting in increased water loss and decreased moisture retention; from the above results, it can be seen that rapid rehydration can effectively form a uniform and stable emulsion, which can quickly form a moisturizing layer on the skin surface and improve the skin's moisture. The emulsion formed by rapid rehydration can quickly provide the skin with the nutrients and active ingredients required, and promote the skin's self-repair process.
[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A freeze-dried powder composition with anti-aging and repairing functions, characterized in that: The freeze-dried powder composition comprises the following raw materials: 1 to 2 parts of polyoxyethylene stearate, 10 to 15 parts of propylene glycol, 5 to 10 parts of squalane, 1 to 2 parts of acrylamide grafted hydroxyethyl cellulose, 0.1 to 0.5 parts of sodium citrate, 0.5 to 1 part of vitamin E, 0.5 to 1 part of vitamin C, 1 to 2 parts of natural extracts, 5 to 10 parts of polyethylene glycol-trehalose eutectic and 80 to 100 parts of deionized water; The specific preparation steps of the polyethylene glycol-trehalose co-crystal are as follows: B1: adding polyethylene glycol to deionized water, stirring and mixing evenly to obtain a polyethylene glycol solution; adding trehalose to deionized water, stirring and mixing evenly to obtain a trehalose solution; B2: Add the trehalose solution prepared in step B1 to the polyethylene glycol solution, heat in a water bath and gradually increase the temperature to 60-70°C at 5°C / min, then maintain the temperature and stir the reaction. After stirring, naturally cool to room temperature, adjust the pH to neutral, perform ultrasonic treatment, filter, wash with cold ethanol, and freeze-dry in vacuum to constant weight to obtain polyethylene glycol-trehalose co-crystals.
2. A freeze-dried powder composition with anti-aging and repairing function according to claim 1, characterized in that: The specific preparation steps of the acrylamide grafted hydroxyethyl cellulose are as follows: A1: Add hydroxyethyl cellulose to deionized water and stir until completely dissolved to obtain a hydroxyethyl cellulose solution; add acrylamide to deionized water and stir until completely dissolved to obtain an acrylamide solution; dissolve ammonium persulfate and N,N'-methylenebisacrylamide in deionized water to obtain an initiating solution; A2: Add the initiating solution prepared in step A1 to the hydroxyethyl cellulose solution, continue stirring to mix evenly, then add the acrylamide solution prepared in step A1, stir and mix evenly, heat in a water bath to control the temperature, and after the reaction is completed, quickly cool to room temperature in an ice bath, dialyze in a dialysis bag, and vacuum freeze-dry to constant weight to obtain acrylamide-grafted hydroxyethyl cellulose.
3. A freeze-dried powder composition with anti-aging and repairing function according to claim 2, characterized in that: The volume ratio of the trehalose solution to the polyethylene glycol solution in step B2 is 1:1 to 1.
5.
4. A freeze-dried powder composition with anti-aging and repairing function according to claim 3, characterized in that: The ultrasonic treatment setting parameters in step B2 are 20-40kHz, power 30-60W, and time 10-20min.
5. A freeze-dried powder composition with anti-aging and repairing function according to claim 4, characterized in that: The ratio of the amount of ammonium persulfate, N,N'-methylenebisacrylamide and deionized water in step A1 is 0.04-0.06 g:0.02 g:30 mL; the volume ratio of the initiating solution, hydroxyethyl cellulose solution and acrylamide solution in step A2 is 1:1:1-2.
6. A freeze-dried powder composition with anti-aging and repairing function according to claim 5, characterized in that: The natural extract is prepared by mixing green tea, turmeric, centella asiatica and chamomile in a mass ratio of 1:0.7:0.8:1.2 through conventional technical means.
7. A method for preparing the freeze-dried powder composition with anti-aging and repairing functions according to any one of claims 1 to 6, characterized in that: The specific preparation steps are as follows: S1: Squalane, vitamin E and polyoxyethylene stearate are mixed according to weight parts, heated and stirred to completely dissolve, and an oil phase is obtained; propylene glycol and sodium citrate are dissolved in deionized water according to weight parts, stirred and dissolved evenly, acrylamide grafted hydroxyethyl cellulose is slowly added, heated in a water bath, stirred thoroughly until dissolved evenly, and then vitamin C and natural extracts are added, and stirring is continued until mixed evenly to obtain an aqueous phase; S2: slowly adding the oil phase prepared in step S1 to the water phase, stirring for reaction, homogenizing and cyclically treating, and stirring again after the treatment is completed to obtain emulsion A; S3: When the temperature of the emulsion A prepared in step S2 drops to 40°C, add polyethylene glycol-trehalose co-crystals, continue stirring until uniformly dispersed, and obtain emulsion B; cool the emulsion B to 0°C at a rate of 0.5-1°C / min, then cool it to -40--50°C at a rate of 1-2°C / min, maintain the temperature for 1-2h, then heat it to room temperature and dry it to constant weight to obtain a lyophilized powder composition.
8. The method for preparing a freeze-dried powder composition with anti-aging and repairing functions according to claim 7, characterized in that: The specific operating parameters of adding the oil phase to the water phase in step S2 are: stirring at 500-800 rpm for 30-60 min at 60-70° C. using a magnetic stirrer, and then homogenizing and circulating for 3-5 times, with setting parameters of 300-500 bar, temperature at room temperature, and each treatment for 2 min. After the homogenization treatment is completed, stirring again at 500-1000 rpm for 10 min.
Citation Information
Patent Citations
Freeze-dried powder, solvent and application of freeze-dried powder and solvent
CN110237022A
Composition and application thereof in preparation of cosmetics and medical instruments
CN113712842A
Composition with skin repairing and enhancing effects as well as preparation method and application thereof
CN117379336A
Composition with barrier enhancing and anti-aging effects as well as preparation method and application thereof
CN117679348A
A freeze-dried composition and preparation thereof
EP4197523A1